2017
DOI: 10.18632/oncotarget.20300
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 rs290481 T>C polymorphism is associated with an increased risk of type 2 diabetes mellitus and fasting plasma glucose level

Abstract: Genetic polymorphisms of the transcription factor 7-like 2 (TCF7L2) gene may be key agents in the etiology of type 2 diabetes mellitus (T2DM). In the present case-control study, we aimed to assess the possible relationship of TCF7L2 polymorphisms with T2DM and determine the effect of TCF7L2 polymorphisms on the level of fasting plasma glucose (FPG) in Eastern Chinese Han subjects. The TCF7L2 rs7903146C>T and rs290481 T>C polymorphisms were genotyped by SNPscan genotyping assays in 502 subjects with T2DM and 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In this SNP, we found that the rs290481TC and TC/CC genotype of TCF7L2 gene is relevant to increased susceptibility and progress of AEG. In additional, we also found that the potential association was more significant in BMI ≥24 kg/m 2 , which was in line with the findings of those studies mentioned above …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this SNP, we found that the rs290481TC and TC/CC genotype of TCF7L2 gene is relevant to increased susceptibility and progress of AEG. In additional, we also found that the potential association was more significant in BMI ≥24 kg/m 2 , which was in line with the findings of those studies mentioned above …”
Section: Discussionsupporting
confidence: 92%
“…In additional, we also found that the potential association was more significant in BMI ≥24 kg/m 2 , which was in line with the findings of those studies mentioned above. 14,26,27 In this study, the relationship between rs1799817 G > A (NM_000208.2:c.3255C > T) polymorphism in the INSR gene and AEG risk was also explored. We found that INSR rs1799817 G > A polymorphism might confer the risk to AEG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor 7-like 2 ( TCF7L2 ) gene plays an important role in various processes, including the activation of target genes in the Wnt signalling pathway [ 34 ], pancreatic β cell proliferation, and glucose homeostasis [ 35 ]. In addition, TCF7L2 is the most significant and consistently replicated gene associated with an increased risk of T2DM [ 34 ].…”
Section: Single or Multiple Gene Studiesmentioning
confidence: 99%
“…For example, evidence for the linkage of Chromosomes 2 and 5 with T2DM was found in females only [ 23 ]. Female-specific associations with T2DM were demonstrated for multiple genes, such as CDKN2A/2B , KCNJ11 , and TCF7L2 [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Male-specific associations with T2DM also involved various genes, such as TCF7L2 , ELMO1 , and BCL11A [ 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%